IMPLEMENTASI APLIKASI ANDROID UNTUK SISTEM PENDAFTARAN DAN ANTRIAN PADA POLI COVID RSUD DORIS SYLVANUS - Putu Bagus Adidyana Anugrah Putra; Viktor Handrianus Pranatawijaya; Nova Noor Kamala Sari; Widiatry Widiatry (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2022)
Application Registration and Application of Queues at the Mobile-Based Covid Poly Hospital of Doris Sylvanus was built because service system offline while doing covid-19 test and vaccination at the Doris Sylvanus Hospital, it was found that there was a build-up of public queues so that it became less efficient for the queuing system and the information conveyed, so many people were less interested in conducting covid-19 test and vaccinations at the Covid Poly Hospital Doris Sylvanus. In this research, the software development method is used waterfall. In the program modeling, several charts are described, including Use Case Diagrams, Activity Diagrams, and Class Diagrams.The application and website creation phase of this study used Android Studio, Firebase, XML, Java, PHP, Javascript, CSS, and JSON. As for System testing in this study uses a blackbox testing system. With the construction of the Mobile-Based Registration and Application Queue Application at the Covid Poly RSUD Doris Sylvanus, this results in a queuing system and registration application, and it is hoped that it can help optimize the services available at the Covid Poly RSUD Doris Sylvanus.